A Novel LC‐MS/MS Assay for Quantification of Des‐carboxy Prothrombin and Characterization of Warfarin‐Induced Changes - Abdul Basit; Bhagwat Prasad; Joanne K. Estergreen; Daniel E. Sabath; Nathan Alade; David L. Veenstra; Allan E. Rettie; Kenneth E. Thummel (Clinical and Translational Science, 2020)
Warfarin is a narrow therapeutic index anticoagulant drug and its use is associated with infrequent but significant adverse bleeding events. The international normalized ratio (INR) is the most commonly used biomarker to monitor and titrate warfarin therapy. However, INR is derived from a functional assay, which determines clotting efficiency at the time of measurement and is susceptible to technical variability. Protein induced by vitamin K antagonist‐II (PIVKA‐II) has been suggested as a biomarker of long‐term vitamin K status, providing mechanistic insights about variation in the functional assay. However, the currently available antibody‐based PIVKA‐II assay does not inform on the position and number of des‐carboxylation sites in prothrombin. The assay presented in this paper provides simultaneous quantification of carboxy and des‐carboxy prothrombin that are essential for monitoring early changes in INR and, thus, serves as the superior tool for managing warfarin therapy. Additionally, this assay permits the quantification of total prothrombin level, which is affected by warfarin treatment. Prothrombin recovery from plasma was 95% and the liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) assay was linear (r2 = 0.98) with a dynamic range of 1–100 µg/mL. The assay interday precision was within 20%. A des‐carboxy peptide of prothrombin (GNLER) was negatively correlated with active prothrombin (Pearson r = 0.99, P < 0.0001), whereas its association was positively linked with INR values (Pearson r = 0.75, P < 0.015). This novel LC‐MS/MS assay for active and inactive prothrombin quantification can be applied to titrate anticoagulant therapy and to monitor the impact of diseases, such as hepatocellular carcinoma on clotting physiology.